THE TERM AL-HADID IN CLASSICAL AND CONTEMPORARY INTERPRETATION (COMPARATIVE STUDY OF THE QUR'AN & ITS TAFSEER AND TAFSIR MAFATIH AL GHAIB) - Milsih, Ira Saputra; Fitri, Widia; Masuwd, Mowafg Abrahem (Universitas Muhammadiyah Surakarta, 2022)
This prompted the author to put forward how the interpretation of verses related to Al-Hadid in the Koran according to the book of the Koran and its Tafsir by the Ministry of Religion of the Republic of Indonesia as a book of contemporary commentaries and Mafatih al-Ghaib by ar-Razi as a classical commentator. The goal is how to analyze the similarities and differences in the interpretation of the Koran and its Tafsir and Mafatih al-Ghaib. The type of research that the author uses is (Library Research) which is qualitative in nature which originates from the Koran, commentary books and books related to the studies that the author examines. The results of this study indicate that the similarities between the Qur'an and its Tafsir and Mafatih al-Ghaib in interpreting Qs al-Isra verse 50, Qs al-Kahf verse 96, Qs al-Hajj verse 21, Qs Saba verse 10 and Qs al-Hadid verse 25 are both explain the utilization of iron. Meanwhile, the difference is found in Qs al-Hadid verse 25, Qs al-Kahf verse 96 and Qs Saba verse 10. According to the Qur'an and its interpretation, iron is one of the elements that functions to transport acids from the lungs to all body tissues, known as iron. Meanwhile, ar-Razi interprets Qs al-Hadid verse 25 that iron is a weapon that can uphold justice and become a sanction for those who violate Islamic law. Then ar-Razi interprets Qs al-Kahf verse 96 that it is a miracle given by Allah to Zulkarnain and finally in Qs Saba verse 10 ar-Razi explains that the iron has been heated with a very hot hell fire.